PENGEMBANGAN FLIPBOOK INTERAKTIF BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI EKOSISTEM UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS X SMA - Nur Muthimmul Faidah, Zulfa; Kuntjoro, Sunu; Ichsan, Mochammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to increase students’ learning motivation in Biology for Grade X of senior high school. The problem identified by the researcher is that students often feel bored and lack enthusiasm during the learning process, which leads to a decrease in their learning motivation. One way to improve this learning motivation is by developing an interactive flipbook based on PBL on ecosystem material that is valid, effective, and practical. The interactive flipbook is able to create a more engaging learning experience, so that students become more enthusiastic, motivated, and active during learning. This research uses the 4D model (define, design, develop, and disseminate) and was tested on a limited scale involving 33 Grade X students at SMAN 17 Surabaya. Validity was measured based on validation results from two Biology expert lecturers, with an overall average percentage score of 97.58% (very valid). Effectiveness was measured based on the results of implementation observations and students’ learning motivation assessed by two observers during learning, obtaining an overall average percentage score of 98% (very strong). The students’ learning motivation questionnaire administered at the end of learning obtained an overall average percentage score of 99.36% (very strong). This was further supported by an analysis of the improvement in classical learning mastery results between the pretest, which obtained an average percentage score of 12.12% (not effective), and the posttest, which obtained an average percentage score of 100% (very effective). Practicality was measured based on the results of the student response questionnaire administered at the end of learning, obtaining an overall average percentage score of 99.40% (very practical). In conclusion, the developed interactive flipbook is considered highly valid, effective, and practical for increasing the learning motivation of Grade X senior high school students.